A Shannon Entropy Approach to the Temporal Evolution of Sep Energy Spectrum - Damiani, A (2012)
The kinetic energy spectra of solar energetic particle (SEP) events contain information on the particle acceleration mechanisms. A novel approach is proposed to investigate the time evolution of the spectral shape for the 20 February 2002 SEP event. Proton differential fluxes recorded by the ERNE instrument aboard SOHO, in the energy range 1.67-112MeV, are analyzed. The solar source is associated with this SEP event by studying solar and interplanetary conditions during the considered time period. The energy spectrum evolution is studied by evaluating the time history of Shannon s differential entropy derived from the SEP fluxes. Our findings suggest that particle acceleration in the considered event is produced by a perpendicular shock in the solar corona. Moreover, dropouts in the particle flux are clearly identified up to energies of at least ?10MeV. © Author(s) 2012.